PENGARUH PENGETAHUAN TENTANG ISU – ISU LINGKUNGAN DAN KEPRIBADIAN (INTROVERT-EKSTROVERT) TERHADAP PERILAKU BERTANGGUNGJAWAB LINGKUNGAN DI SMAN 1 BEKASI - Ariksrikiana Ariksrikiana; Suwirman Nuryadin; Sunaryo Sunaryo (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2018)
This study aims to determine the effect of knowledge on environmental issues and personality (introverts) towards environmentally responsible behavior. The method used in this study is an ex-post-facto study. This study was conducted at SMAN 1 Bekasi, with 40 respondents Students.Research and development has been applied by involving 40 people as sample,each for treatment and control group Instrumet for measuring people knowleage has been developed in true-false format with reability research results revealed that there was significant difference of people knowleage between post and pre-test in treatment group between treatment and control group gain-scores. These indicated that instructional package was able to improve effectively people knowleage abaut natural reasource conservasion.sasi culture has been proven to be one of traditional heritages which influence people way of live howto harmonioussly with nature.it has been also strengthened by a intergrating it with ecological concepts in an intsructional package this product could be disseminated for young generation as what expected by sustainable development, The results of the study show that there is an influence of environmental issues on the personality of environmentally responsible behavior. The conclusion that knowledge of environmental issues is not alone affects the environmentally responsible but also depends on the personality (introvert and extrovert) hali it can also be seen in the findings.